(untitled) (Transactions on Additive Manufacturing Meets Medicine, 2020)
With advancements in electronics technology, the new-era of devices are flexible and bendable. This has given rise to new smart textiles as wearables. Printed electronics enables to put down electronics on textiles without affecting the flexibility of the fabric. We have developed dry electrodes on healthcare stockings to stimulate muscles to preserve muscle mass in COVID-19 patients. The fabric does not allow direct printing of electronics. Thus, various layers are used. This paper investigates the mechanical strength of these layers on the stocking to remain functional for daily usage. We also discuss washing results on the layers.